Identifying which clients will cancel their insurance policy machine learning methods - Narain, K.; Pang, Y. (Proceedings - 2024 IEEE 48th Annual Computers, Software, and Applications Conference, COMPSAC 2024, 2024)
Using the 2013 data set provided by Insurance Inc., logistic regression and linear discriminant analysis models were created along with data visualizations to find out which factors recorded in the data set and the state of those factors causes a client to cancel their policy. The factors that impact whether a client will cancel are those that directly pertain to the policy. For example, the coverage type and the premium the client is paying for the policy impacts the probability the client will cancel their policy. Factors that go into forming the policy and have a relationship between one another such as age and premium, also impact the probability that a client will cancel their policy. The credit status of a client, whether it is low, medium, or high, and the type of coverage they have, has the most impact on a client's inevitability to cancel. If a client's credit score is classified as low, then that client is has a high probability of cancelling their policy according to the LDA (Linear Discriminant Analysis) classifier and logistic regression model. Likewise, if a client has coverage type B, the probability that they will cancel their policy is higher. The sales channel used to sell a client a policy also impacts the probability they will cancel. According to the LDA classifier and the logistic regression model, if a client was sold a policy over the phone, they are more likely to cancel. © 2024 IEEE.
Keywords: Gaussian Distribution; Linear Discriminant Analysis (LDA) Classifier; Logistic Regression; Naive Bayes Classifier; dept.mat

Language Learning Outcomes in on Ground Vs. Online Settings: Comparison and Correlation - Tu, I Ju; Bartlett, Andrew (American Journal of Distance Education, 2024)
While the effectiveness of online instruction has been well established, there remains a limited understanding of the correlation between language skills and performance across various instructional sections. This study investigates the language proficiency outcomes of college students in online and on-ground language instruction, focusing on four essential language skills: Reading, Writing, Listening, and Speaking. Data were collected from students enrolled in third-semester language courses in French, German, Italian, and Spanish during the Spring semesters of 2019 and 2021 with on-ground and online instruction respectively in a public university in the United States. Descriptive statistics, the Kruskal-Wallis test, and pairwise correlation analysis were used to analyze the students’ performance in both modalities. The results indicate that students generally outperformed in the online modality, demonstrating a significantly higher positive correlation range compared to on-ground instruction. This finding suggests that multi-modality language instruction has the potential to foster more integrated and cohesive language proficiency development. The implications firstly show the positive correlation range in the online modality indicates that college instructors may be more capable of implementing effective online teaching methods due to various reasons. Secondly, college students’ potential for self-directed learning in the online setting may contribute to their enhanced outcomes. However, the study also reveals challenges for less taught languages, such as the need for additional support in terms of resource curation and networking opportunities for instructors.
_eprint: https://doi.org/10.1080/08923647.2024.2366594
Keywords: dept.mat; peer-reviewed

Reactive axillary lymph nodes after COVID-19 mRNA vaccination: Comparison of mRNA vs. attenuated whole-virus vaccines - Adin, M.E.; Isufi, E.; Wu, J.; Pang, Y.; Nguyen, D.; Simsek Has, D.; Caner, C.; Aboueldaha, N.; Mossa-Basha, M.; Pucar, D. (Nuclear Medicine Communications, 2024)
Objective To compare the incidence and natural course of reactive axillary lymph nodes (RAL) between mRNA and attenuated whole-virus vaccines using Deauville criteria. Methods In this multi-institutional PET-CT study comprising multiple vaccine types (Pfizer-BioNTech/Comirnaty, Moderna/Spikevax, Sinovac/CoronaVac and Janssen vaccines), we evaluated the incidence and natural course of RAL in a large cohort of oncological patients utilizing a standardized Deauville scaling system (n=522; 293 Female, Deauville 3-5 positive for RAL). Univariate and multivariate analyses were conducted to evaluate the predictive value of clinical parameters (absolute neutrophil count [ANC], platelets, age, sex, tumor type, and vaccine-to-PET interval) for PET positivity. Results Pfizer-BioNTech/Comirnaty and Moderna vaccines revealed similar RAL incidences for the first 20 days after the second dose of vaccine administration (44% for the first 10 days for both groups, 26% vs. 20% for 10-20 days, respectively for Moderna and Pfizer). However, Moderna recipients revealed significantly higher incidences of RAL after 20 days compared to Pfizer-BioNTech/Comirnaty, with nodal reactivity spanning up to the 9th week post-vaccination (15% vs. 4%, respectively P<0.001). No RAL was observed in patients who received either a single dose of J&J vaccine or two doses of CroronaVac. Younger patients showed increased likelihood of RAL, otherwise, clinical/demographic parameters were not predictive of RAL (P=0.014 for age, P>0.05 for additional clinical/demographic parameters). Conclusion RAL based on strict PET criteria was observed with mRNA but not with attenuated whole-virus vaccines, in line with higher immunogenicity and stronger protection offered by mRNA vaccines. © 2024 Wolters Kluwer Health. All rights reserved.
Keywords: COVID-19; CoronaVac; Janssen; axillary lymph node; dept.mat; mRNA vaccine; peer-reviewed

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed